Role of alkaline-earth metal in catalysed imine hydrogenations - De Tobel, Bart; Hamlin, Trevor A.; Fonseca Guerra, Célia; Harder, Sjoerd; De Proft, Frank; Alonso, Mercedes (Polyhedron, 2024)
Alkaline-earth metal (Ae) catalysts have been recently developed for challenging imine and alkene hydrogenation at moderate reaction conditions, providing a sustainable alternative to transition metal catalysis. The understanding of catalytic hydrogenations mediated by group 2 metals is underdeveloped and mechanistic studies are scarce from experimental and computational sides. Herein, we examine the role of the metal on the catalytic hydrogenation of imines by Ae[N(SiMe3)2]2 (Ae = Mg, Ca, Sr, Ba) using state-of-the-art computational techniques. Trends in energy barriers and turnover frequencies agree remarkably well with the experimentally observed increase in catalytic activity upon descending group 2 (Mg ≪ Ca < Sr < Ba). Structural and chemical bonding differences in the key intermediates were found to be the main driving force behind the enhanced reactivity of heavier Ae catalysts. More specifically, the N-Ae-H^ bond angle is drastically reduced in the Ca, Sr, and Ba catalytic species driven by the participation of the d-orbitals in the chemical bonding. The activation strain model reveals that these catalytic reactions are strain controlled and the higher activation barriers for the Mg catalyst originates from unfavourable bond angles in the Mg hydride species featuring linear structures and a more covalent metal-hydride bond. Further decomposition of the interaction energy reveals that stronger repulsive interactions destabilize the Mg species, indicating that the steric congestion due to the small Mg centre impedes reaction kinetics. Overall, the different aspects to be considered in the Ae catalyst design for imine hydrogenations are the strength and flexibility of the Ae-H bond, the bond ionicity, the N-Ae-H^ angle and the strength of the noncovalent interactions in the TOF-determining intermediate.
CRIS-Team Scopus Importer:2023-12-15